In situ utilization of generated electricity for nutrient recovery in urine treatment using a selective electrodialysis membrane bioreactor. (2nd November 2017) - Wang, Yun-Kun; Geng, Yi-Kun; Pan, Xin-Rong; Sheng, Guo-Ping
Graphical abstract: Highlights: An electrodialysis membrane bioreactor was developed for urine treatment. C, N, P and S in urine could be removed simultaneously in the EDMBR system. Phosphate and sulfate separation and selective recovery from urine were achieved. The EDMBR showed high potentiality for urine desalination. Abstract: Recovering resources, especially energy and nutrients, from source-separated urine, is attracting increasing interest. By integrating electrodialysis into an electrochemical membrane bioreactor, a novel, selectively electrodialysis membrane bioreactor (EDMBR) was developed for the treatment of source-separated urine and nutrient recovery. Before injection into the EDMBR system, the diluted urine was pretreated by ammonia stripping. The concentration of ammonia in the urine decreased from 1292.2 ± 47.5 mg/L to 235.1 ± 5.7 mg/L upon stripping, denoting an 81.8% ammonia removal efficiency. Phosphate and sulfate recovery from urine were then achieved in situ, utilizing the electricity generated by selective electrodialysis in the EDMBR. In this EDMBR system, which was fed with treated urine after stripping, a maximum power density of 23.5 W/m 3 was obtained at an external resistance of 1000 Ω. Consequently, 97.4% of the NH4 +, 76.7% of the PO4 3−, and 94.5% of the SO4 2 − was removed, while 65% of the phosphate and 54.9% of the sulfate (based on their amounts in urine after stripping) were recovered as a concentrated solution. Moreover, other salts, especially NaCl, were selectively retained as brine, indicating that the EDMBR shows promise for urine desalination. This study demonstrates a new strategy for nutrient separation and recovery from source-separated urine by utilizing bioelectricity generated in situ .